NOVA OCORRÊNCIA DE LIVONECA REDMANNI (ISOPODA: CYMOTHOIDAE) NO LITORAL NORDESTE DO BRASIL: New occurrence of Livoneca redmanni (Isopoda: Cymothoidae) in the northeast coast of Brazil - Mota Alves, André; Freitas Freire, Janaína; Palmeira dos Santos, Tatiana Maria; Madi, Rubens Riscala (Arquivos de Ciências do Mar, 2023)
The occurrence records of parasitic isopods on the northeast coast of Brazil have increased in recent years, however the species occurring and their distribution on the coast are still not fully known, which makes occurrence records important for future monitoring to be carried more accurately. Thus, this study aimed to report a new occurrence of Livoneca redmanni Leach, 1818 (Cymothoidae), providing a complete morphological description and addressing some aspects of its distribution. The fish analyzed in the present study were acquired at points of sale and analyzed in the laboratory. Only two fish were parasitized with one isopod each. The low prevalence indicates that this type of infestation may be related to competition for resources, generating a factor that does not allow the co-occurrence of more than two specimens of the parasite per host. The morphological characteristics of the collected specimens were in accordance with the descriptions present in the scientific literature. In conclusion, in the present study, a new occurrence in the biogeographic status of L. redmanii in the northeastern coast of Brazil, the state of Sergipe, is presented, contributing to the knowledge of the distribution of this crustacean in the Brazilian coast.